An assessment of decision to change lifestyle in cardiovascular patients after hospitalization - Makar, Anita (Array, 2019)
The aim of this study was to examine the lifestyle of cardiovascular patients with different diagnoses, as well as the willingness to change lifestyle after hospitalization. These results can significantly influence everyday nursing practice during rehabilitation and education of cardiovascular patients and increase motivation to change risk behavior. The participants of the study were the patients at the Cardiology Department of the Special Hospital for Medical Rehabilitation Krapinske Toplice (N=70). In assessing their lifestyle before the hospitalization most participants agreed with the statements „I was often tense, angry or concerned about the events in the society“ and „I was often tense, angry or worried while following the media“. Rural participants compared to those from urban areas estimated their lifestyle before hospitalization statistically as more risky. Most participants decided to change their lifestyle compared to the habits they had before hospitalization. They mostly agree with the statements related to the decision of reducing cigarette consumption and walking more. Older participants brought significantly less decisions of changing lifestyle after hospitalization. Furthermore, there were no significant differences in the decision to change lifestyle in terms of gender, work activity and professional occupation. Participants with arrhythmia had a statistically significant higher value of lifestyle change compared to those who had myocardial infarction and hypertension. Participants with bypass had a statistically significant higher value of decision to change lifestyle compared to those who were hospitalized because of arrhythmia. These results are useful for identifying groups of patients where nurses need to make additional efforts to encourage motivation to change risky lifestyle.